Application of Biomi Technology in Processing Livestock Waste into Quality Organic Fertilizer in “Sekar Pasti Wangi” Livestock Group, Petiga Village, Marga District, Tabanan Regency - Rukmini, Ni Ketut Sri; Sutapa, I Gede; Suwitari , Ni Ketut Etty (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Cattle husbandry produces a substantial quantity of cow manure that has not been utilized to its full potential. To date, cow manure has only been stored without proper processing, resulting in environmental problems such as an offensive odor and damage to the environment's aesthetics. According to the results of the survey, participants lack the necessary knowledge and skills to convert livestock waste, such as cow dung, into valuable and useful organic fertilizer. The goal is to impart knowledge regarding the transmutation of cow manure into high-quality organic fertilizer and its use on plants. In addition to observing the impact of technology's application on partners, the method used to conduct face-to-face activities, counselling, and direct practice will involve observing the impact of technology's application on partners. These measures will be implemented progressively. First, we will provide fundamental guidance regarding biomedical technology for the production of high-quality organic fertilizer from animal waste. Second, we will provide hands-on training on the use of biomes in the production of high-quality organic fertilizer from livestock waste and conduct multiple evaluations. The livestock producers of Sekar Pasti Wangi are physically capable of producing high-quality organic fertilizer. In terms of the economy, the sale of organic fertilizers has increased the income of farmers. Due to the conversion of cow manure into organic fertilizer, the environmental pollution produced by cow manure is reduced by 95% as a result of this activity.